Pentingnya Kode Etik Seorang Guru di Yayasan Ibnu Al Mubarak - A, Adriani (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This service is related to the importance of understanding a teacher's code of ethics in the Ibnu Al Mubarak Islamic Foundation environment. This activity aims to 1) educate teachers about the code of ethics of a teacher in an Islamic school, 2) form and provide an understanding of the many cases of violations of the code of ethics of teachers in Islamic schools and 3) provide guidance to teachers routinely after the service is carried out. The method used in this activity is counseling through providing information, namely the lecture and response methods. This activity is carried out offline by providing this information through a written invitation to the Ibnu Al Mubarak Foundation. The results of this counseling activity, the teachers who were participants who attended received education through counseling which showed an increase in participant knowledge regarding the importance of a teacher's code of ethics, especially in the Islamic Foundation environment, marked by the lively discussion of the teacher's code of ethics.